2007
DOI: 10.1016/j.ejcts.2007.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of normothermic organ bath and verapamil–nitroglycerin solution alone or in combination on the blood flow of radial artery

Abstract: Hypothermia plays an important role in radial artery vasospasm. Normothermic organ bath and verapamil-nitroglycerin solution alone or in combination relieve spasm of radial artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In a study with 20 patients, Tarhan et al [6] compared the use of scissors, electrocautery, and ultrasonic cautery for harvesting time, spasm, and electron microscopic endothelium examination and found all the results between the groups to be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with 20 patients, Tarhan et al [6] compared the use of scissors, electrocautery, and ultrasonic cautery for harvesting time, spasm, and electron microscopic endothelium examination and found all the results between the groups to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…It is often recommended to prepare the RA with the accompanying veins within the pedicle in order to prevent the occurrence of spasm. Harmonic scalpel (Harmonic scalpel ® , HS, Ethicon Endo-Surgery, Cincinnati, Ohio) and electrocautery (Petaş ® Profesyonel Elektronik, Ankara, Turkey) are reported to be suitable devices for this technique [6] . Skeletonized harvesting of RA using sharp dissection is a less frequently used method [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…The organ bath technique is mainly used for preventing radial artery spasm as described in previous studies. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Schena et al (5) reported a case of the nongrafted right coronary artery spasm treated with decisive balloon dilatation and stent insertion, which was intractable with intracoronary infusion of nitroglycerin and CCB. As observed in the Tarhan and colleagues' study, to prevent spasm of grafting artery, donor vessel should be manipulated carefully to minimize surgical trauma during harvest, endothelial injury must be avoided by maintaining the blood flow until just before distal anastomosis, body temperature and temperature of harvested vessel have to be strictly controlled as normothermia, and medication such as nitroglycerin and/or CCB also should be applied systemically or topically (7). …”
Section: Discussionmentioning
confidence: 99%